Association between Antioxidant Enzymes and Breast Cancer - Fathima, Kumar Pragulbh, Nayan Jyoti Deka, Ranjan Kumar, B. Prabasheela*, Anuj Kumar Singh, Asra (Recent Research in Science and Technology, 2011)
<span style="font-family: ";Arial Narrow";,";sans-serif";; color: black; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-ansi-language: EN-US; mso-bidi-font-family: Calibri; mso-bidi-language: AR-SA;">The exact antioxidant status in breast cancer patient is still not clear. So present study was focused on enzymic antioxidants such as Superoxide dismutase, Catalase, Glutathione-S-transferase, Glutathione peroxidase and Glutathione reductase in the serum of 25 histopathologically proven breast cancer patients. When the data were analyzed with age matched control the antioxidant levels were found to decrease indicating enhanced free radical activity in breast cancer patients while the antioxidant defense mechanism is weakened. However further elaborate clinical studies are required to evaluate the role of such antioxidant enzymes in breast cancer management.